2017
DOI: 10.1002/2211-5463.12183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of murine polyspecific monoamine transporters

Abstract: The dysregulation of monoamine clearance in the central nervous system occurs in various neuropsychiatric disorders, and the role of polyspecific monoamine transporters in monoamine clearance is increasingly highlighted in recent studies. However, no study to date has properly characterized polyspecific monoamine transporters in the mouse brain. In the present study, we examined the kinetic properties of three mouse polyspecific monoamine transporters [organic cation transporter 2 (Oct2), Oct3, and plasma memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…5C) are similar to prior studies (Hayer-Zillgen et al, 2002), where corticosterone preferentially bound to hOCT3 (IC 50 = 0.6 μM) relative to hOCT2 (IC 50 ≈ 80 μM). Corticosterone is also a poor blocker of hPMAT-driven transport (Engel, Zhou, & Wang, 2004; Russ, H. et al, 1993), as supported by its observed IC 50 ≈ 1 mM in our experiments, and in the literature (Engel et al, 2004; Miura et al, 2017). The consistency of our results with the literature establishes an important platform on which to perform comparative analyses of D22 analogs in human transporter expressing cell lines.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…5C) are similar to prior studies (Hayer-Zillgen et al, 2002), where corticosterone preferentially bound to hOCT3 (IC 50 = 0.6 μM) relative to hOCT2 (IC 50 ≈ 80 μM). Corticosterone is also a poor blocker of hPMAT-driven transport (Engel, Zhou, & Wang, 2004; Russ, H. et al, 1993), as supported by its observed IC 50 ≈ 1 mM in our experiments, and in the literature (Engel et al, 2004; Miura et al, 2017). The consistency of our results with the literature establishes an important platform on which to perform comparative analyses of D22 analogs in human transporter expressing cell lines.…”
Section: Discussionsupporting
confidence: 88%
“…Mouse models are an essential preclinical resource to study the action of low-affinity transporters. Functional similarities have been observed between the uptake kinetics of substrates like dopamine, MPP + , and serotonin by human and mouse PMAT (Miura et al, 2017; Shirasaka et al, 2016). On the other hand, hOCT3 and mOCT3 were found to share similar affinities for MPP + , but not serotonin (Massmann et al, 2014).…”
Section: Discussionmentioning
confidence: 86%
“…These studies suggest that "uptake 2" mechanisms, putatively OCT3, may play a significant role in 5-HT signaling and homeostasis, particularly when SERT function is reduced [147,152,153]. Further, uptake by OCT2 [154,155] and OCT3 is inhibited by corticosterone [148,156,157]. Therefore, hormonal interference of "uptake 2" clearance in later life could contribute to stressexacerbated symptoms of autism, especially during perceived stressful social situations in cases where these secondary transporters may have been permanently upregulated to compensate for impaired SERT function.…”
Section: Preclinical Evidence For "Uptake 2" Transporters In Serotonimentioning
confidence: 99%
“…Expression of PMAT is greater in brain than in other organs, and PMAT is more highly expressed in brain than other uptake 2 transporters (Dahlin, Xia, Kong, Hevner, & Wang, 2007;Duan & Wang, 2010;Engel, Zhou, & Wang, 2004;Miura et al, 2017). Therefore, loss of PMAT function might have more pronounced behavioural effects than those observed in mice lacking an OCT.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the polyspecific uptake 2 transporters exhibit differential affinities for monoamine neurotransmitters. PMAT preferentially transports serotonin and dopamine, whereas OCTs display higher affinities for histamine, epinephrine and norepinephrine (Duan & Wang, ; Miura et al., ). Thus, serotonergic and dopaminergic signalling in brains of PMAT‐deficient mice might be prolonged, although this has not yet been directly investigated.…”
Section: Introductionmentioning
confidence: 99%